Allegory and imperial power in Orwell’s Animal Farm: A postcolonial critique of U.S. hegemony in the Middle East - Abdul Wahab, Mohammad Osman; Saleh, Shoeb; AlAli, Rommel Mahmoud; Abdullatif, Ali; Ismail, Sayed M (Research Journal in Advanced Humanities, 2026)
Animal Farm has too often been secured within a closed Cold War referentiality, as though its force depended entirely on translating pigs, horses, and slogans back into the chronology of Soviet communism. This essay argues that Orwell’s novella remains politically exact in a different way. Its afterlife lies in the formal intelligence with which it narrates the capture of emancipatory language, the conversion of law into exception, the management of fear, and the normalization of hierarchy under the sign of collective necessity. Reading the novella through postcolonial criticism, allegory theory, discourse analysis, and a contrapuntal method indebted to Edward Said, I treat Animal Farm not as a prophetic key to later history but as a portable allegorical grammar through which certain mechanisms of U.S. hegemony in the Middle East become legible. The argument does not identify Orwell’s characters with specific states or leaders, nor does it flatten Iraq, Palestine, Gulf security regimes, and the post-9/11 order into a single script. Rather, it shows how the novella’s slogans, revised Commandments, developmental spectacles, staged emergencies, and final crisis of visible difference illuminate recurring imperial procedures: elite capture, proxy sovereignty, epistemic management, legal elasticity, and the narration of violence as protection. At the same time, the essay keeps the limits of allegorical transfer in view and reckons with Orwell’s own Cold War appropriation by Anglo-American power.